Ética y filosofía del derecho en Kant y su influencia en la Declaración Universal de los Derechos Humanos - Alvarado Dávila, Víctor (2008)
What we propose to do in this text is find out now Kant makes the leap from Ethics to Law. In the second place, highlight what we call “The kantian Ethical Revolution” a revolution that brings us to the ideal application of Cosmopolitan Law, with its one and only purpose: Perpetual Peace. And lastly, we will try to demonstrate the influence of the kantian ideals and ethical principals in the Universal Declaration of Human Rights.